From Socialization to Collaboration: Community Engagement in the UNNES Special Purpose Forest Area (KHDTK), Mount Ungaran, for Conservation and Sustainable Use - Martono, S.; Rahayuningsih, Margareta; Khoiruddin, Moh.; Ngabiyanto, Ngabiyanto; Ahmad, Tsabit Azinar; Suminar, Suminar (Universitas Negeri Semarang, 2026)
The designation of the UNNES Special Purpose Forest Area (KHDTK) at Mount Ungaran has brought new opportunities and uncertainties for communities living adjacent to the forest, particularly in Desa Ngesrepbalong, Kendal Regency. Many residents were not fully informed about the change in forest governance, the boundaries of the KHDTK, or their potential roles in its management. This community service program aimed to strengthen local understanding and encourage collaborative engagement in conservation and sustainable utilization of the forest area. The activities were conducted through coordination with local authorities, socialization sessions, field visits, and participatory discussions involving village officials, forest farmer groups, and community representatives. Data were gathered through observation, interviews, and feedback forms to assess changes in knowledge and attitudes. The program found that direct dialogue and joint field supervision of forest boundaries significantly reduced community concerns, particularly among coffee farmers previously involved under the Perhutani scheme. The transition from one-way socialization to participatory collaboration helped build mutual trust and opened pathways for sustainable partnership between the university and local stakeholders. It is recommended that follow-up programs focus on structured community-based forest management schemes, continuous mentoring, and integration of conservation principles into local economic activities to ensure long-term sustainability.